ANALISIS TATANAN MASYARAKAT PADA GANG MUSHOLLA LINGKUNGAN LIMA TANJUNG MORAWA - Najla Hapipah Lubis; Erlina Pohan; Muthomainnah Sitorus; Robiyatul Adawiyah Hasibuan; Puja Zulhaini; Lidia Safitri; Nurjannah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the social order of the community in Gang Musholla Lingkungan Lima, Pekan Subdistrict, Tanjung Morawa District, Deli Serdang Regency, as well as to examine the forms of social interaction, values, norms, and cultural practices that persist in the area. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The research informants consisted of community leaders and the head of the *perwiritan* group residing in Gang Musholla Lingkungan Lima. The findings Indicate that the social structure of the community is still predominantly characterized by strong kinship patterns, while social relations among residents are built upon values of mutual cooperation, tolerance, and social solidarity. Religious activities such as, along with the use of the musholla as a center of social interaction, play an important role in maintaining social norms and fostering collective awareness among community members. However, this study also identifies challenges in the form of value changes resulting from technological development, a decline in the intensity of direct interaction among younger generations, and shifts in the role of community leaders in local decision-making processes. Overall, the social order in Gang Musholla Lingkungan Lima continues to reflect the characteristics of a traditional community with cohesive social patterns, while undergoing a process of social adaptation toward a more modern social structure. This study is expected to serve as a reference for social and community studies and as a basis for the development of locally based community empowerment programs.